Metody komunikacji z widzem teatralnym w teatrze publicznym w Opolu w latach 1945-1974= Methods of communication with the audience in public theater in Opole (1945-1974) - Michalak, Hubert (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article explores the promotional methods of the public theatre in Opole within the period of 1945-1975. In the three decades following WWII, the institution operated as: Teatr Miejski im. Juliusza Słowackiego, Scena Opolska Teatrów Śląsko-Dąbrowskich and Państwowy Teatr Ziemi Opolskiej respectively. In 1975 the theatre is granted the new headquarters and is named Teatr im. Jana Kochanowskiego.
Keywords: teatr; Opole; promocja; PR; theatre; promotion